Biederman et al (2019) polar lipid profile - Biederman, Amanda M.; Kuhn, Donald E.; O'Brien, Kristin M.; Crockett, Elizabeth L. (Dryad Digital Repository, 2019)
Polar lipid profile of mitochondrial membranes prepared from cardiac ventricle of Chaenocephalus aceratus, Notothenia coriiceps, and Pseudochaenichthys georgianus. Measurements were performed in animals collected in the region of the Western Antarctic Peninsula during the austral fall season of 2015.